Minimalist Sape: The Use of Digital Sound Effects For a Musical Hybrid Concept Between Dayak Sape Music and Minimalist Music - Darlene, Esther (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2023)
Sape Minimalist music composition is the result of a musical dialogue between Sape (Dayak) music and Minimalist music through a hybrid approach. Minimalist music itself is a backlash mainly against the chaos and complexity of serialism and aleatoric music. In minimalist music, short melodic patterns with clear tonality and constant repetition are the main focus. In this Minimalist Sape composition, the Sape instrument is usually played for specific functions such as accompanying ritual ceremonies/customs, as well as entertainment, in this composition Sape collaborates with minimalist music elements and produces a repertoire that can be classified in the "absolute" music category. The hybrid musical dialogue approach, which combines two different types of music, has the ability to increase the variety and uniqueness of Sape music. Hybrids in Minimalist Sape compositions produce unique new musical variations with an experiment using a touch of digital sound effect technology that the tempo development of sape music assisted by other music can affect the hybrid concept realized by combining musical elements from Dayak Sape music with Minimalist music. The method used in this research was conducted through a literature review, previous repertoire review, and using an artistic-based research approach. The results of the composition found that Sape - Minimalist music using digital sound effect applications can bring breakthroughs with the concept of musical hybrids from Sape music and Minimalist music with a touch of sound design effects that produce music with new creativity.